A study on mechanical properties of Al5052/CFRP/Al5052 composite through three-point bending tests and shear lap tests according to surface roughness. (May 2020) - Lee, MS; Kim, SJ; Lim, OD; Kang, CG
In this study, aluminum samples with various microsurface roughness values were produced by sandblasting to investigate the effect of the Ra (Surface roughness) value on the samples' mechanical properties. Toward this end, a carbon fiber reinforced plastic/Al5052 hybrid sample was produced, and its mechanical properties were investigated through a tensile test, three-point bending test, and shear lap test. The theoretical and experimental tensile strength values of the hybrid composite were compared. During the bending test, CFRP and AI5052 separated in untreated specimens. A side-view examination revealed that the adhesion was best when the surface roughness was greatest ( Ra  = 1.2 µm). Furthermore, shear load increased with the surface roughness. Therefore, the surface treatment was a crucial factor in making the specimen surface even and in increasing the roughness and therefore improving adhesion.